Supporting students’ understanding of equivalent fractions using jelly - Laela Sagita; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Budi Mulyono (Beta: Jurnal Tadris Matematika, 2022)
Fraction as part-whole is the key to further fractional understanding, such as equivalent fractions. A problem faced by students in equivalent fractions is that they understand one part without including the other parts. This article discusses how 4th-grade students understand fractions as part-whole and equivalent fractions using units of equivalent. Indonesian Realistic Mathematics Education-oriented learning environment using jelly context was developed and tested in two stages, involving six students with different levels of mathematics ability. The analysis of group discussions and students’ answers to the given tasks shows that students with low abilities have difficulty showing that 1/4 is one part of the four parts. The students only know fractions in a/b form without understanding their meaning. It impacts the construction of equivalent fractions as units of equivalent. High-ability students can easily do mathematization on 2/8 or 2/6 by making a cut pattern before cutting the jelly. The research contributes to learning design that begins with activities related to the fractions as part-whole.